Children’s positive feelings at school during post-pandemic COVID-19: An exploratory research with photo elicitation interview - Faiz Fatihul 'Alwan; Tuti Azizah; Ridha Fauzia Rimuna (Institut Agama Islam Negeri Langsa, 2022)
Two years since the beginning of the pandemic, and now it is starting to subside, the face-to-face learning system has been applied as usual. Changes in the learning system, from online to face-to-face learning, change the atmosphere and conditions of the learning environment. Then, the conditions affected students’ experiences and feelings during the learning process. This study uses a qualitative approach with photo-elicitation interviews (PEI) to explore the positive feelings of four elementary school students in Bandung. PEI explores the experiences of children who struggle to describe their situation explicitly. The interactive data analysis found that there was a change in the positive feelings experienced by students in the hybrid learning and back-to-school phases. Interaction with peers and the learning process with teachers are the two dominant things that trigger children’s positive feelings about learning in the post-COVID era.